Pengaruh Ekstrak Babawangan (Fimbristylis miliacea) pada Perkecambahan dan Pertumbuhan Bobontengan (Leptochloa chinensis) - Nisa, Citra Khoirrun; Pujisiswanto, Hidayat; Pramono, Eko; Sembodo, Dad Resiworo Jekti (JURNAL AGROTROPIKA, 2024)
Chinese sprangletop (Leptochloa chinensis) reproduces sexually and vegetatively. This weed has a lot of seeds, is easy to grow, and adapts well to dry and wet land. Proper control is needed. Hoorahgrass extract can be used as an alternative to control weeds. Hoorahgrass (Fimbristylis miliacea) is a group of enigmatic weeds that contain allelochemical compounds. The aims of this research were to determine the effect of the source and concentration of hoorahgrass extract on the germination and growth of chinese sprangletop. This research carried out at the Greenhouse Integrated Field Laboratory, Faculty of Agriculture, University of Lampung from December 2022 to February 2023 using a Randomized Block Design (RAK) with 2 factors and 4 replications. The first factor was the extract component of hoorahgrass root (A1), shoot (A2) and mixture (A3), and the second factor was hoorahgrass with a concentration of 0% (B0) or (control), 2.5% (B1), 5% (B2 ), 7.5% (B3), 10% (B4). The data obtained were analyzed using analysis of variance, and first tested for homogeneity of variance using the Bartlett test, followed by the least significant difference test (LSD) at the 5% level. Based on the research results, hoorahgrass extract concentration of 5 to 10% was most effective in reducing seed germination rate, seed germination speed, chinese sprangletop root length and total dry weight. A concentration of 10% was most effective for reducing the height of chinese sprangletop. Keyword: Fimbrisylis, concentration, extract, bioherbicide, Leptochloa